Insecurity and Food Crisis in Nigeria: A Study of 2009-2022 - Gbamwuan, Asor (Journal of Advanced Research in Humanities and Social Sciences, 2022)
One of the challenges that face Nigeria between 2009 and 2022 is insecurity. Within this short period, Nigeria experienced various dynamism of security problems including Boko-Haram insurgency, Banditry, cattle rustling, farmers-herders squabbles, separatist movements, militancy, religious bigotry et cetera with gross implications for the socio-economic development of the nation. Against this backdrop, the study establishes the nexus between insecurity and the food crisis in Nigeria as a social problem that truncates national economic growth and development. The study’s methodological approach is evidence-based from a desk review of extant literature which has been corroborated with primary sources for objectivity. The study revealed that BokoHaram terrorism, banditry, farmers-herders conflicts have distorted agriculture production by peasant farmers, government programmes, policies. The result is increased hunger and malnutrition, escalation of food prices, unemployment, social vices. To stem this tide, the study suggested the adoption of current technology to fight insecurity by the government, recruitment and training of the Nigerian military, reevaluation of the existing government agricultural policies. How to cite this article: Gbamwuan A. Insecurity and Food Crisis in Nigeria: A Study of 2009-2022. J Adv Res Humani Social Sci 2022; 9(4): 31-41.